APLIKASI FILTER KONTEN YOUTUBE DENGAN PEMANFAATAN GOOGLE API - Fuad, Ahmad; Razaq, Jefri Alfa (Information Technology and Telematics, 2018)
API, YouTube, PHP Abstract YouTube is one of the most famous video sharing websites in the world. About hundreds of millions of internet users visit this site every day, almost all video content is on YouTube but not all are filtered according to their respective categories. One of them is educational content video, in the world of visual media education in the form of video is quite effective for school students to be interested to learn. At the elementary school level can be used for learning media preparation in facing national exams every year, various video tutorials how to do the national exam questions, grilles and how to quickly do the exam questions almost all in YouTube. The existence of the YouTube Data API service to access and retrieve video data from YouTube can be used to create a website-based application in the form of a video content filter on YouTube, especially educational content that aims to learn the national exam preparation for elementary school students according to the subjects being tested. The html programming language, php, javascript and notepad ++ software can make this application.